Patient empowerment: a critical evaluation and prescription for a foundational definition - Varela, Antonio J.; Gallamore, Michael J.; Hansen, Noah R.; Martin, Dakota C. (Frontiers in Psychology, 2025)
IntroductionThe evolution of healthcare continues to display an incongruence between delivery and outcomes. Current healthcare paradigms for patient empowerment warrants analysis. A lacking operational application for and agree upon assessment of patient empowerment contributes to healthcare’s incongruence. Interchangeable psychosocial concepts and specific patient contextual factors associated with health-related behavioral change have escaped an applicable definition of empowerment. The aim of this theoretical perspective review is to support a comprehensive and contextual understanding of patient empowerment that frames a definition for future consensus research.Methods and mechanismsA theoretical perspective review of patient empowerment including interchangeable concepts and patient contextual factors such as personal suffering and resilience; self-determined meaning and purpose; and autonomy, competence, and self-efficacy are critically analyzed. This analysis builds on adjacent concepts including therapeutic alliance, communication, motivation, and trust. The inclusion of specific patient contextual factors that relate to behavioral change elevate the need to reinforce coping and self-management skills as mechanism for patient empowerment. Practice gaps for those experiencing chronic disease, pain, and mental health disorders in rehabilitation setting are specific populations who benefit from healthcare providers unifying the variables associated with patient empowerment.Results and discussionThe review of associated concepts synthesized an actionable definition of patient empowerment that serves as a foundation for future research. Behavior related changes occur through the evolution in one’s identity, perceptions, and abilities. Interventions that inspire autonomy, competence, and relatedness with a renewed sense of purpose establish resilience and self-efficacy. The totality of this inspired self-determined plan of care establishes the mechanisms required for behavioral change and sustainable transformation. The cumulative experience becomes patient empowerment.